Optimization of RSA Algorithm by using Binary Method - Singh, Raushan Kumar; Kumar, Shobhit (International Journal of Computer Sciences and Engineering, 2014)
This paper proposes a calculation method for the improvement of RSA algorithm which reduces the issues of scalability, flexibility and performance. This paper will be based on the mathematical function used in the RSA algorithm and reduces the number of steps for calculating the value of Md. The proposed method improves the calculation performance of the RSA to make it useful in providing security to every known application.